Case Report: Interindividual variability and possible role of heterozygous variants in a family with deficiency of adenosine deaminase 2: are all heterozygous born equals? - Pulvirenti, Federica; Cinicola, Bianca Laura; Ferrari, Simona; Guadagnolo, Daniele; Sculco, Eleonora; Capponi, Martina; Loffredo, Lorenzo; Sciannamea, Maddalena; Insalaco, Antonella; Quinti, Isabella; De Benedetti, Fabrizio; Zicari, Anna Maria (Frontiers in Immunology, 2023)
Deficiency of adenosine deaminase 2 (DADA2) is a rare systemic autoinflammatory disease, typically with autosomal recessive inheritance, usually caused by biallelic loss of function mutations in the ADA2 gene. The phenotypic spectrum is broad, generally including fever, early-onset vasculitis, stroke, and hematologic dysfunction. Heterozygous carriers may show related signs and symptoms, usually milder and at an older age. Here we describe the case of two relatives, the proband and his mother, bearing an ADA2 homozygous pathogenic variant, and a heterozygous son. The proband was a 17-year-old boy with intermittent fever, lymphadenopathies, and mild hypogammaglobulinemia. He also had sporadic episodes of aphthosis, livedo reticularis and abdominal pain. Hypogammaglobulinemia was documented when he was 10 years old, and symptoms appeared in his late adolescence. The mother demonstrated mild hypogammaglobulinemia, chronic pericarditis since she was 30 years old and two transient episodes of diplopia without lacunar lesions on MRI. ADA2 (NM_001282225.2) sequencing identified both mother and son as homozygous for the c.1358A>G, p.(Tyr453Cys) variant. ADA2 activity in the proband and the mother was 80-fold lower than in the controls. Clinical features in both patients improved on anti-tumor necrosis factor therapy. An older son was found to be heterozygous for the same mutation post-mortem. He died at the age of 12 years due to a clinical picture of fever, lymphadenitis, skin rash and hypogammaglobulinemia evolving toward fatal multiorgan failure. Biopsies of skin, lymph nodes, and bone marrow excluded lymphomas and vasculitis. Despite being suspected of symptomatic carrier, the contribution of an additional variant in compound heterozygosity, or further genetic could not be ruled out, due to poor quality of DNA samples available. In conclusion, this familiar case demonstrated the wide range of phenotypic variability in DADA2. The search for ADA2 mutations and the assessment of ADA2 activity should be considered also in patients with the association of hypogammaglobulinemia and inflammatory conditions, also with late presentation and in absence of vasculitis. Furthermore, the clinical picture of the deceased carrier suggests a possible contribution of heterozygous pathogenic variants to inflammation.